A Grading System For The Prediction Of Unilateral Chronic Subdural Hematoma Recurrence After Initial Single Burr Hole Evacuation - Shen J; Xin W; Li Q; Gao Y; Zhang J (Dove Medical Press, 2019)
Jun Shen,1–3,* Wenqiang Xin,2,3 Qifeng Li,2,3,* Yalong Gao,2,3,* Jianning Zhang2,3 1Department of Neurosurgery, Yijishan Hospital of Wannan Medical College, Wuhu City, Anhui 241001, People’s Republic of China; 2Department of Neurosurgery, Tianjin Medical University General Hospital, Tianjin 300052, People’s Republic of China; 3Key Laboratory of Post-Trauma Neuro-Repair and Regeneration in Central Nervous System, Ministry of Education, Tianjin, 300052, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianning ZhangDepartment of Neurosurgery, Tianjin Medical University General Hospital, Tianjin 300052, People’s Republic of ChinaTel/fax +86 2260814359Email jianningzhang@hotmail.comBackground and purpose: Previous studies have identified many risk factors related to the recurrence of chronic subdural hematomas (CSDHs). Among these factors, there may be deviations in measuring the midline shift, preoperative hematoma volume (PreHV), postoperative hematoma residual volume, and postoperative pneumocephalus in bilateral CSDHs. The aims of this study were to eliminate the impact of complicated situations on parameter measurement and to identify actual predictors for CSDH recurrence, and finally, to develop a grading system to predict unilateral CSDH (uCSDH) recurrence.Patients and methods: A total of 342 patients with uCSDH were identified. Predictors of uCSDH recurrence were obtained from univariable and multivariable logistic regression models. A prognostic grading system was developed based on the results of multivariable logistic regression and receiver operating characteristic (ROC) analyses. All patients were scored according to the grading system, and differences in the recurrence rate were reanalyzed according to the scores.Results: Age, antiplatelet or anticoagulant use, midline shift, severe brain atrophy, drainage volume, and the ratio of the postoperative pneumocephalus volume (PostPV) to the postoperative hematoma cavity volume (PostHCV) were identified as independent risk factors for predicting the recurrence of uCSDH. The cut-off values of age, drainage volume, midline shift, and the ratio of the PostPV to the PostHCV were 67 years, 101 mL, 11.2 mm, and 31.61%, respectively. The recurrence rates were 1.7%, 12.4%, 19.4%, 53.3%, and 58.3% for scores of 0–1, 2, 3, 4, and 5–6, respectively, which significantly increased as the score increased (P<0. 001).Conclusion: The prognostic grading system for uCSDH on the basis of multivariable logistic regression and ROC analyses is applicable and reliable.Keywords: brain atrophy, chronic subdural hematoma, Glasgow Coma Scale, Glasgow Outcome Scale, grading system, recurrence rate